2015
DOI: 10.1097/dss.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Full-Thickness Skin Grafts for Lower Leg Defects

Abstract: Full-thickness skin graft is an effective method of repairing defects on the lower leg after removal of cutaneous lesions. The aftercare of FTSG was acceptable with 86% of patients requiring 5 or fewer visits to secondary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
0
24
0
2
Order By: Relevance
“…Fifteen articles met the inclusion criteria involving only skin surgery (for details see Table S1, Supplemental Digital Content 4, http://links.lww.com/DSS/A423. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Three studies used randomization, [28][29][30] and 4 studies compared a no tie-over dressing with a tie-over dressing but did not always specify the materials used for the bolster. 27,29,31,33 Two articles mentioned both STSGs and FTSGs and did not subdivide the graft take per technique.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen articles met the inclusion criteria involving only skin surgery (for details see Table S1, Supplemental Digital Content 4, http://links.lww.com/DSS/A423. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Three studies used randomization, [28][29][30] and 4 studies compared a no tie-over dressing with a tie-over dressing but did not always specify the materials used for the bolster. 27,29,31,33 Two articles mentioned both STSGs and FTSGs and did not subdivide the graft take per technique.…”
Section: Search Resultsmentioning
confidence: 99%
“…28,38 Thirteen studies used only FTSGs. [25][26][27][29][30][31][32][33][34][35][36][37]39 The graft defect size was described in different measurements of length (mm and cm) or surface area (mm 2 and cm 2 ) and varied from 8 mm in length (smallest) 34 to 52.4 cm 2 (largest area). 25 Nine studies reported the use of additional antibiotics: systemic 35 and local.…”
Section: Search Resultsmentioning
confidence: 99%
“…Flap and graft reconstruction are the types of surgeries associated with the highest risk for SSI . Graft take in lower leg surgeries have been reported at rates of 64% to 90%, depending on the study . The risk of bleeding complications has previously been reported to be between 0.3% and 3% and for necrosis between 1.7% and 8.6% …”
Section: Discussionmentioning
confidence: 99%
“…1,18 Graft take in lower leg surgeries have been reported at rates of 64% to 90%, depending on the study. 13,22,23 The risk of bleeding complications has previously been reported to be between 0.3% and 3% 1,5,16 and for necrosis between 1.7% and 8.6%. 1,5 Honaker et al 6 evaluated the complication risk of 69 patients in below-knee Mohs surgery, with an overall complication rate of 17%, of which 50% were infections, 3.25% delayed wound healing, 2.17% hypergranulation, and 8% hypertrophic scars.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excisions on the leg pose a series of challenges. The elliptical excision is generally considered the option of choice when possible, with advantages of simple design, widespread application on most parts of the leg and ease of specimen orientation if further excision is required . However, an elliptical excision may result in excessive tissue tension and an inability to close the defect.…”
Section: Introductionmentioning
confidence: 99%